Hubungan Kepatuhan Konsumsi Tablet Tambah Darah dengan Kejadian Anemia pada Remaja Putri di SMK Batik 2 Surakarta - Septiani, Fitroh Rindi; Setiyaningrum, Zulia (Universitas Batanghari Jambi, 2025)
The purpose of this study was to analyze the relationship between compliance in consuming blood supplement tablets and the incidence of anemia in adolescent girls. This study used cross sectional design. The population of this study were students of SMK Batik 2 Surakarta with a total of 165 students. The sample in this study was selected using simple random sampling method as many as 60 respondents. The inclusion criteria were adolescent girls who were not menstruating and aged 15-18 years. Data on adherence to consumption of blood supplement tablets were collected by conducting interviews and filling out questionnaires on adherence to consumption of blood supplement tablets. Data on the incidence of anemia was obtained by checking hb levels using the cyanmethemoglobin method. Relationship analysis using Chi-Square test. The results showed that there were 30 people (53,6%) adolescent girls who were not anemic. In addition, the number of young women who did not adhere to the consumption of blood supplement tablets who were anemic was also high, as many as 26 people (46,7%). The results of the Chi-Square test is that there is no relationship between adherence to consumption of blood supplement tablets and the incidence of anemia in adolescent girls at SMK Batik 2 Surakarta.